Penguatan Dakwah Inklusif Berbasis Antropologi: Program Pengabdian kepada Masyarakat di Yayasan Peduli Tali Bangsa Ciputat - Aspriansyah, Aspriansyah; Jaelani, Misnan; Sobirin, Sobirin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Da'wah, as an effort to spread religious values, plays a crucial role in building an inclusive and tolerant society. However, da'wah practices are often exclusive and neglect the socio-cultural context of the recipients. This study aims to evaluate and describe the implementation of anthropology-based inclusive da'wah through a community service program at the Peduli Tali Bangsa Foundation in Ciputat. The method used was a qualitative approach using participatory observation, in-depth interviews, and documentation studies. The results indicate that understanding the cultural anthropology of the local community is key to developing an inclusive, adaptive, and relevant da'wah approach. This program has successfully increased public awareness of the values ​​of tolerance, social engagement, and concern for differences.